Developing IT Strategic Planning Using Mobile Enterprise Architecture In The Academic Process of Atma Jaya Makassar University - Tungadi, Astrid Lestari; Suharjito, Suharjito (ComTech: Computer, Mathematics and Engineering Applications, 2017)
The purpose of this research was to examine the feasibility of the development of mobile enterprise strategic plan, analyze the academic process and the utilization of information technology (IT), and generate documentation IT strategic planning by implementing Mobile Enterprise Architecture in the academic process of Atma Jaya University in Makassar. Data were taken from distributing questionnaires to 297 respondents and conducting interviews to 18 respondents. Data were examined using SWOT analysis, the incorporation of academic scorecard analysis and IT balanced scorecard analysis, financial analysis, as well as analytic hierarchy process (AHP). SWOT analysis results indicate that case study is in a weak position, which possibly never take advantage of opportunities since the weakness of the stand or the power is not enough to work on it. In addition, the results of the performance analysis of the utilization of information technology using the Balanced Scorecard analysis show that the average performance is sufficient. The result of documentation of IT strategic planning was analyzed with financial analysis indicating the feasibility of implementation because it provides benefits for university of 141,32%. Furthermore, Analytic Hierarchy Process (AHP) to determine the priority of IT strategy proposals shows that the main priority is to develop portal for student and lecturer.